2005
DOI: 10.1002/ijc.21512
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the epidermal growth factor receptor by erlotinib (Tarceva™) for the treatment of esophageal cancer

Abstract: Esophageal cancer is the sixth most common cause of cancerrelated death worldwide. Because of very poor 5-year survival new therapeutic approaches are mandatory. Erlotinib (Tarceva TM ), an inhibitor of epidermal growth factor receptor tyrosine kinase (EGFR-TK), potently suppresses the growth of various tumors but its effect on esophageal carcinoma, known to express EGFR, remains unexplored. We therefore studied the antineoplastic potency of erlotinib in human esophageal cancer cells. Erlotinib induced gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 37 publications
6
39
1
1
Order By: Relevance
“…p21 plays an essential role in growth arrest after DNA damage, while its overexpression leads to cell cycle arrest, which prevents DNA damage (17). Erlotinib-mediated signaling is involved in the up-regulation of p21 (18). We demonstrated the overexpression of p21 in erlotinib-resistant cells (A549/ ER cells) when compared to A549 cells (Fig.…”
mentioning
confidence: 71%
“…p21 plays an essential role in growth arrest after DNA damage, while its overexpression leads to cell cycle arrest, which prevents DNA damage (17). Erlotinib-mediated signaling is involved in the up-regulation of p21 (18). We demonstrated the overexpression of p21 in erlotinib-resistant cells (A549/ ER cells) when compared to A549 cells (Fig.…”
mentioning
confidence: 71%
“…We also showed that tumor p21 waf immunostaining at baseline was correlated with clinical response to neoadjuvant erlotinib. In squamous cell carcinoma cell lines, the cytostatic effect of erlotinib is mediated by p21 waf (26). Furthermore, it has been reported that loss of p21 waf expression is correlated with poor prognosis in squamous cell carcinoma (27).…”
Section: Discussionmentioning
confidence: 99%
“…UM-22B, PCI-15B, and 1483 cells were treated with a range of doses of the inhibitors for 72 h, and MTT assays were performed to assess cell viability. The time point and range of doses used were selected based on kinetics experiments (data not shown) and previously published reports Seki et al, 2006;Sutter et al, 2006). Data were normalized to untreated control cells, and the percentage of cytotoxicity and IC 50 values were calculated as described under Materials and Methods.…”
Section: Scchn Cell Lines Demonstrates Similar Ic 50 Values For Gossymentioning
confidence: 99%